Public Theology as a Theology of Resilience in Sub-Saharan Africa: A Public Pastoral Care Contribution - Nanthambwe, Patrick (Religions, 2024)
The negative impacts of COVID-19, the ongoing war between Russia and Ukraine, political unrest, and natural disasters in sub-Saharan Africa have caused widespread suffering. In light of these crises, many have questioned the relevance of theology in addressing such complex challenges. This article tackles critical questions such as: How can public theology effectively engage with the socio-political and economic issues facing sub-Saharan Africa? What role does public pastoral care play in fostering resilience within these communities? Can theology provide tangible support in the face of widespread suffering, and if so, how? The article argues that public theology offers a resilient framework to guide communities through these difficult times, particularly when integrated with public pastoral care. Public theology can provide hope, support, and a sense of purpose to those affected by engaging both spiritual and social dimensions. The article further explores how public pastoral care, as a practical expression of public theology, can address individuals’ and communities’ emotional, psychological, and spiritual needs. Ultimately, it demonstrates that public theology is relevant and essential in fostering resilience and promoting human flourishing in the face of adversity.